Concurrent Pancreatic and Sartorius Muscle Lipomas: A Case Report - Om Prakash Bhattaa; Shritik Devkotab; Arun Kalikotec; Prakash Gyawalid; Sachin Awasthie (Clinical Case Reports)
ABSTRACT We present an incidentally diagnosed case of concurrent pancreatic and Sartorius muscle lipoma in a 65‐year‐old female with cholelithiasis. Such dual presentation has seldom been mentioned in the literature and requires thorough evaluation to differentiate it from other pathologies.